Chronology and documentary handbook of the State of Louisiana - Vexler, Robert I. (Dobbs Ferry, N.Y. Oceana Publications, 1978)
Contains a chronology of historical events from 1519 to 1977, a biographical directory of prominent citizens, and copies of pertinent documents.
Includes bibliographical references (p. [137]-139) and index.
Keywords: Louisiana -- History -- Chronology; Louisiana -- Biography; Louisiana -- History -- Sources